2021
DOI: 10.1101/2021.02.17.431610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escherichia colirobustly expresses ATP synthase at growth rate maximizing concentrations

Abstract: Improved protein expression is an important evolutionary adaptation of bacteria. A key question is whether evolution has led to optimal protein expression that maximizes immediate growth rate (short-term fitness) across conditions. Alternatively, fitter genetic variants could display suboptimal short-term fitness, because they cannot do better or because they strive for long-term fitness maximization by, for instance, anticipating future conditions. To answer this question, we focus on the ATP-producing enzyme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Indeed, significant evidence exists that expression of metabolic proteins in E. coli (and other bacteria) is close to 'optimal' under conditions of nutrient excess, in the sense that any deviation from the observed wild-type expression results in a decrease of the instantaneous growth rate. [35,[42][43][44][45][46][47][48]…”
Section: The Expression Of Anticipatory Proteins Reduces the Instanta...mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, significant evidence exists that expression of metabolic proteins in E. coli (and other bacteria) is close to 'optimal' under conditions of nutrient excess, in the sense that any deviation from the observed wild-type expression results in a decrease of the instantaneous growth rate. [35,[42][43][44][45][46][47][48]…”
Section: The Expression Of Anticipatory Proteins Reduces the Instanta...mentioning
confidence: 99%
“…That is, metabolic proteins often exhibit expression levels such that the instantaneous growth rate is maximized under the studied growth condition. [35,[42][43][44][45][46][47][48][49][50] For example, it was recently shown that E. coli expresses its F 1 F 0 -ATPase, a protein complex that uses the proton-motive force to regenerates ATP, at optimal levels across more than 25 conditions. [43] Figure 2 exemplifies the effect of modulating F 1 F 0 -ATPase expression on the growth rate for growth on glucose, showing that the WT growth rate indeed corresponds to the growth rate of the mutant with optimal F 1 F 0 -ATPase expression.…”
Section: Expression Of Metabolic Enzymes Often Maximises the Instanta...mentioning
confidence: 99%
See 2 more Smart Citations